2015
DOI: 10.1186/s41043-015-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding practices and associated factors among HIV positive mothers in Southern Ethiopia

Abstract: The objective of this study was to assess complementary feeding practices and associated factors among HIV exposed infants in Sidama Zone, Southern Ethiopia. An institutional based cross-sectional study with cluster random sampling technique was employed and all HIV exposed infants aged 6-17 months found in randomly selected health institutions in Sidama zone, Southern Ethiopia were included. A 24-hour dietary recall and 7-day quasi-food group frequency was used to assess complementary feeding practices. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
5
10
1
Order By: Relevance
“…As compared to mothers/ caregivers who achieving maximum schooling (ten and above), illiterate mothers/ caregivers were less likely to initiate complementary food at six months of age. This finding is nearly consistent with findings from southern Ethiopia (Sidama zone), Northern Ethiopia (Mekele), Pakistan, South India and five European countries 14 , 15 , 19-21 but finding from Nepal, Lebanon and Axum, north Ethiopia 16 , 18 , 22 reports that educational status did not show statistical significance. This may be due to as educational status increase; better knowledge they have and easily aware of new information and put into practice.…”
Section: Discussionsupporting
confidence: 89%
“…As compared to mothers/ caregivers who achieving maximum schooling (ten and above), illiterate mothers/ caregivers were less likely to initiate complementary food at six months of age. This finding is nearly consistent with findings from southern Ethiopia (Sidama zone), Northern Ethiopia (Mekele), Pakistan, South India and five European countries 14 , 15 , 19-21 but finding from Nepal, Lebanon and Axum, north Ethiopia 16 , 18 , 22 reports that educational status did not show statistical significance. This may be due to as educational status increase; better knowledge they have and easily aware of new information and put into practice.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that HIV positive mothers who had adequate knowledge on infant feeding were 1.8 times more likely to have recommended way of infant feeding practice than those who had inadequate knowledge which is supported by a study conducted in Guraghe zone, that showed 1.9 times more likely to have recommended way that can be justified by similarity in age and health care service they might got throughout the country [8, 10]. This finding is in line with similar researches conducted in Addis Ababa and Mekele due to the fact that, in most low income countries female headed families face economic problems that hinder them to have appropriate feeding choice [11]. Moreover, families with nobody to take care or supported by grandparent might fail in setting necessary economical support that makes the difference from which both parents take over [12].…”
Section: Discussionsupporting
confidence: 71%
“…In this study, the prevalence of timely initiation of complementary feeding among children in 6–24 months of age in Dessie Referral Hospital was 65.1% with 95% CI (59.3%–70.5%), which was in line with studies conducted in public health facilities found in Mekelle Town, Northern Ethiopia (62.8%) [ 4 ], and Lalibela (63%) [ 16 ]. This study finding was higher than the national prevalence (51%) [ 23 ], result from study in India (42.1%) [ 24 ], Nigeria (41%) [ 5 ], Nepal (57%) [ 6 ], and Sidama Zone Southern Ethiopia (42%) [ 7 ]. This difference might be due to sociodemographic character difference, wealth status difference, and activeness of the society.…”
Section: Discussionmentioning
confidence: 63%
“…But most mothers do not start complementary feeding at appropriate time [ 3 – 6 ]. Children are at increased risk of malnutrition starting from six months because breast milk alone is not sufficient to give the required nutrient contents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%